Psychoeducation Strategy: Acceptance and Commitment Therapy (ACT) to Improve Self-Efficacy of Stroke Patients - Tri Wahyuni Ismoyowati; Ratna Puspita Adiyasa (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Stroke is the most common cerebrovascular event. Stroke patients often have biological, spiritual, and psychosocial changes. Psychosocial problems experienced in stroke patients include problems with self-efficacy. Acceptance and Commitment Therapy (ACT) is commonly used to solve psychosocial problems. Objective: This study aims to determine the effect of ACT on the self-efficacy of stroke patients.  Methods: This study utilized quantitative and quasi-experimental designs without a control group. The study was conducted in a selected hospital rehabilitation unit in Yogyakarta. The respondents were selected via the purposive sampling technique. The self-efficacy was assessed using The Strategies Used by Patients to Promote Health (SUPPH) questionnaires and statistically tested with the Wilcoxon test. The total number of respondents of this study was 33 stroke patients. The characteristic of respondents was mostly 45 – 64 years old (72.73% ), male (57.6%) and, had a history of stroke for 1 – 6 months (39 %). Result: Wilcoxon test results showed a computed p-value of 0.000 on the effect of ACT on stroke patients’ self-efficacy; thus, the null hypothesis was rejected. In other words, ACT proves its effectiveness in improving stroke patients’ self-efficacy. Conclusion: Based on the data, this research can be concluded that ACT effectively improved the self-efficacy of stroke patients. The researchers recommend utilizing ACT as a nursing intervention for stroke patients in the hospital rehabilitation unit.